The slope-intercept form: y = mx + b
m - slope
b - y-intercept
We have 2(x - 1) = y + 3 use distributive property
(2)(x) + (2)(-1) = y + 3
2x - 2 = y + 3 subtract 3 from both sides
2x - 5 = y → y = 2x - 5
slope: m = 2
y-intercept: b = -5
x-intercept for y = 0. Substitute:
2x - 2 =0 add 2 to both sides
2x = 2 divide both sides by 2
x = 1
Answer:
slope = 2
y-intercept = -5
x-intercept = 1
-------------------------------------------------------------
y = 2x + 1
slope: m = 2
y-intercept: b = 1
x-intercept for y = 0. Substitute:
2x + 1 = 0 subtract 1 from both sides
2x = -1 divide both sides by 2
x = -0.5
Answer:
slope = 2
y-intercept = 1
x-intercept = -0.5